Attenuation and molecular characterisation of fowl adenovirus serotype 8b isolate of Malaysia in specific-pathogen-free embryonated chicken eggs for future development of vaccine - Mohamed Sohaimi, Norfitriah; Bejo, Mohd Hair; Omar, Abdul Rahman; Ideris, Aini; Mat Isa, Nurulfiza (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Fowl adenoviruses (FAdVs) are the important pathogen in cases of inclusion body hepatitis (IBH) and gizzard erosion in poultry. Nine-day-old specific pathogen free (SPF) embryonated chicken eggs was used for propagation of FAdV serotype 8b isolate of Malaysia up to 15th consecutive passages for future production live attenuated vaccine. The study demonstrated that the FAdV isolate was successfully propagated in SPF embryonated chicken eggs and remained pathogenic with 100% mortality and lesions of hepatic necrosis and hydropericardium. All samples were 99% identical with FAdV group E isolate UPM08158 hexon gene in NCBI blast. Nucleotide (nt) substitution was detected in hexon gene in P5, P10 and P15 where 2nt changes occurred within L1 loop region for P5 and P10 while 1 nt changes in P15 as compared with reference FAdV-E isolate HG. Only one amino acid (aa) substitution was observed in P10 and P15 within L1 loop region at position 276 and 138, respectively (numbering with reference to FAdV-E isolate HG). Based on phylogenetic analysis, the isolate was classified under Group E species with other twenty six published isolates. In fiber gene, all samples were 97% identical with FAdV-8 strain CFA40. Various nt substitutions in P5, P10 and P15 were observed where changes are prominent in P15 with 4nt changes at position 928, 973, 1026 and 1078. For amino acid sequence analysis, 2 aa changes was detected in P15 within knob region at position 377 and 412 (numbering with reference to FAdV-8 isolate 05-50052-3180) as compared to reference FAdV-8 from GenBank. It was classified under FAdV serotype 8 with other twenty published fiber gene isolates. It was concluded that SPF embryonated chicken eggs are sensitive medium for propagation and attenuation of recent FAdV isolate (UPM1137) for consecutive passages with amino acid changes in hexon and fiber gene proteins.